A study of protective effects of Mus81 in preeclampsia: Protective effects of Mus81 in preeclampsia - Wu, Shaojun; Tang, Jing; Wang, Lin (Cellular and Molecular Biology, 2023)
This study was to investigate the effect and mechanism of Mus81 in severe PE. 20 cases of pregnant women with severe PE and 20 cases of healthy pregnant women were enrolled. Placental tissues were collected after delivery, and the expression of Mus81 in placental tissues was detected by qRT-PCR and Western blot (WB). The si-Mus81 adenovirus was used to construct a pregnant mouse model of Mus81 down-expression in vivo, to clarify the effect of Mus81 on pregnant mice and blood pressure, urinary protein, serum sFLT1 and fetal weight in PE. After overexpression of Mus81 in HTRB-S/Vneo cells, the proliferation, migration and apoptosis of the cells were measured by EdU staining, flowcytometry, qRT-PCR and cell scratch test. Protein expression of the Wnt/β-catenin signaling pathway was detected by WB. To further explore the mechanism, Wnt/β-catenin inhibitor DKK1 inhibitor was added to HTRB-S/Vneo cells and then Ad-Mus81 was added for co-incubation for 48 h. Protein expressions p-β-catenin and activated-β-catenin were detected by WB. Bax and Bcl-2 were detected by qRT-PCR, and the proliferation of HTRB-S/Vneo cells was measured by EdU staining. Cell migration was detected by scratch test. The expression of Mus81 in the placental tissues of pregnant women with severe PE was lower than that in normal placental tissues. The blood pressure, urine protein and serum sFLT1 protein levels of Mus81 knockdown mice were all upregulated and the fetal weight was decreased after the injection of si-Mus81, which successfully simulated the characteristics of PE. After overexpression of Mus81, the proliferation and migration of HTRB-S/Vneo cells were enhanced, while the apoptosis was decreased. After overexpression of Mus81, the expression levels of p-β-catenin decreased while active-β-catenin increased obviously. Then, DKK1 inhibitor and Ad-Mus81 were added to the HTRB-S/Vneo cells and co-incubated for 48 h. Compared with the Ad-Mus81+DMSO group, the expression of p-β-catenin increased while activated-β-catenin decreased in the Ad-Mus81+DKK1 inhibitor group. The proliferation and migration decreased, but apoptosis of HTRB-S/Vneo cells was increased. Mus81 can regulate the proliferation, migration and apoptosis of trophoblast cells through the Wnt/β-catenin pathway, which plays an important role in maintaining the normal physiological function of trophoblast cells and is also involved in the occurrence and development of severe PE.